Pengaruh Kepemilikan Manajerial dan Kepemilikan Institusional Terhadap Nilai Perusahaan - Ichwan Syahrul Gunawan; Dirvi Surya Abbas; Triana Zuhrotun Aulia (Jurnal Mutiara Ilmu Akuntansi, 2024)
The purpose of this research is to determine the influence of Managerial Ownership, Institutional Ownership, and Independent Board of Commissioners on Company Value in Food and Beverage sub-sector Manufacturing companies listed on the Indonesia Stock Exchange (BEI). The research time period used was 5 years, namely the 2017-2021 period. The population of this research includes manufacturing companies in the Food and Beverage sub-sector listed on the Indonesia Stock Exchange (BEI) for the 2017-2021 period. The sampling technique uses purposive sampling technique. Based on the predetermined criteria, 12 companies were obtained. The number of samples for this research is 60 samples. The type of data used is secondary data obtained from the Indonesian Stock Exchange website. The data analysis technique used is moderate regression analysis supported by the Eviews 9.0 program. The research results show that Managerial Ownership has an influence on Company Value, while Institutional Ownership shows that together they have no influence on Company Value. Keywords Managerial Ownership, Institutional Ownership Company Value